Inggris - Muhammad Noor Ariefin; Hilda Bahagia, Rosalia; Jelatu, Silfanus (Agriculture, 2024)
Tomatoes are one of the most commonly cultivated vegetables. This vegetable is multipurpose, especially as a daily cooking spice, a raw material for tomato sauce, and has a delicious and slightly sour taste. Considering its still low production, it is necessary to develop cultivation efforts to increase its yield. This study aims to determine the effect of different planting distances on the growth and yield of tomato plants (Solanum lycopersicum L). The research was conducted in La'o Village, Wali Subdistrict, Langke Rembong District, Manggarai Regency, East Nusa Tenggara, from April to July 2024. The method used in this study was a Randomized Block Design, consisting of 4 treatment levels: J1: 50x40 cm, J2: 50x50 cm, J3: 40x30 cm, and J4: 40x40 cm. Each treatment level was repeated 4 times, resulting in 16 experimental units. Each experimental unit contained 10 plants, with a total of 160 plants. Observations were made by examining 5 sample plants per experimental unit, with a total of 80 sample plants. The parameters observed in this study included: plant height (cm), number of leaves (blades), number of branches, flowering age (days), stem diameter (mm), number of harvested fruits (g), and fruit harvest weight (g). The data obtained were analyzed using Analysis of Variance (ANOVA) or F test at the 5% level. If significant differences were found, Duncan's Multiple Range Test was conducted at the 5% level. Research results show that various planting distances do not have a significant effect on all parameters. The ideal planting distance for tomato plants is observed with the following treatments: J3 (40 x 30 cm) for plant height, J2 (50 x 50 cm) for the number of leaves, J1 (50 x 40 cm) for flowering age, stem diameter, and J4 (40 x 40 cm) for the fresh weight of harvested fruit.